PEMANFAATAN ARANG AKTIF BONGGOL JAGUNG (Zea mays) SEBAGAI ADSORBEN RADIKAL ALKIL PEROKSIDA PADA MINYAK JELANTAH : STUDI PENURUNAN BILANGAN PEROKSIDA - Hasriani; Saibun Sitorus; Irfan Ashari Hiyahara (PROSIDING SEMINAR KIMIA, 2025)
Used cooking oil is known to contain lipids resulting from the oxidation process at high heating temperatures. The oxidation process in cooking oil continuously causes the formation of alkyl peroxide radicals. Used cooking oil is at risk of disrupting water and soil ecosystems if disposed of into the environment without further management. In this study, a characterization test of corn cob activated charcoal was carried out based on SNI 06-3730-1995, characterization using the Surface Area Analyzer (SAA) instrument and a test of the peroxide number in used cooking oil. The results of the activated charcoal characterization test showed that it still met the requirements of SNI 06-3730-1995 and showed an increase in surface area of ​​109,705 m2/g in the SAA test. In the control before the adsorption process using corn cob activated charcoal, the peroxide number was 30 mek O2/kg. In the refining process of used cooking oil, there was a decrease in the peroxide number. The optimum decrease in the peroxide number was found at a charcoal mass of 4 g with a contact time of 45 minutes. The peroxide value obtained was 8 mek O2/kg, which was a decrease of around 73.33% from the used cooking oil before refining. Keywords: Activated Charcoal, Alkyl Peroxide Radicals, Surface Area Analyzer, Used Cooking Oil, Zea Mays.